Redefining "Political Islam" in Indonesia: Nahdlatul Ulama and Khittah '26 - Bush, Robin (Studia Islamika, 2000)
Observers of Islam and Muslim politics in Indonesia over the past year could not fail to note the explosion of political parties bearing the banner of Islam as well as the reemergence of a discourse on a "political Islam" and the specter of an Islamic state that became a subject of anxiety among some and enthusiasm among others. This was hardly a new issue-Indonesians have struggled since even before the formation of their state to negotiate the relationship between Islam and the state. Indonesia's founding fathers, upon developing its Constitution, were mired in the debate over the role of Islam and the syari'ah in their new nation. This issue raised its head time and time again at key points during the Soekarno regime-as discussed below. Soeharto artificially muted the potential political role of Islam through enforcement of asas tunggal Pancasila and careful balancing of Islam with the military. Almost immediately after Soeharto fell, however, there was an explosion of political parties bearing the banner of Islam, and the discourse on the shape of the new Indonesian political system was dominated by the debate over the role of Islam.DOI: 10.15408/sdi.v7i2.709